Pengaruh Basis Pemberdayaan Masyarakat Desa Terhadap Kreativitas Kelompok Masyarakat Desa Guna Meningkatkan Taraf Hidup Masyarakat Desa Era Covid-19 - Sitti Rabiah; Lesi Hertati; Lilis Puspitawati; Rilla Gantino; Meifida Ilyas (Indonesia Berdaya, 2021)
The purpose of community empowerment is to determine the equality or equal position between the community and institutions that carry out community empowerment programs, both for men and women. The dynamics that are built are the relationship of equality with the development of mechanisms from knowledge, experience, and also each other's expertise. The results of this study are expected that the community can continue the empowerment program that can stimulate community independence is a program that is participatory, planned, carried out, supervised, and evaluated by the community. But to reach this level requires time and a mentoring process that includes a companion who is highly committed to empowering the community, the creativity of the village community groups to improve the standard of living of the Covid-19 era villagers. It is hoped that the results of this training will allow the community to grow and develop independently in order to improve life expectancy in order to support a better and more prosperous family economy, so as to help the economy get better. The principle of self-reliance is respecting and prioritizing community abilities compared to assistance from other parties. This concept does not view the poor as incapable objects (the save not), but as subjects who have little ability (the have litte). They have the ability to save in-depth knowledge about business problems, know about their environmental conditions, have the workforce and the will and have long-complied social norms. All of these must be explored and used as basic capital for the empowerment process. Assistance from other parties which is material in nature must be seen as a support, so that the provision of assistance does not weaken the level of self-reliance.